Complete ureteral stenosis after ureteroscopic lithotripsy successfully managed using a simultaneous retrograde and antegrade flexible ureteroscopic approach. Issue 1 (11th November 2020) - Miyai, Toshitaka; Kawahara, Takashi; Kuroda, Shinnosuke; Yasui, Masato; Uemura, Hiroji
Abstract: Both retrograde and antegrade approach contributed to the success of a delicate endoscopic procedure. Even when guidewire did not pass thorough to the stenosis lesion, lightning and contrast reagents contributed the way through to the stenosis lesion. Abstract : Both retrograde and antegrade approach contributed to the success of a delicate endoscopic procedure. Even when guidewire did not pass thorough to the stenosis lesion, lightning and contrast reagents contributed the way through to the stenosis lesion